Problems and solutions in quantum mechanics - Tamvakis, K. (Cambridge University Press, 2005)
This collection of solved problems corresponds to the standard topics covered in established undergraduate and graduate courses in Quantum Mechanics. Solutions are presented in considerable detail with emphasis on the principles and methods used, allowing students to master problem-solving techniques. For use as a supplementary text or self-study tool.